So u multiply each term in the first parentheses by each term in the second parentheses.
√5 √5 + 6√5-3√5 - 3x6
Now you multiply the numbers which will get u:
5+6√5 - 3√5 - 18
Then subtract:
-13 +3√5 that’s your answer
I believe the ratio in simplest form is 1.3 to 0.7.
<em>(Please mark this answer as Brainliest and leave a Thanks if I helped you!)</em>
Answer:
49b^2 -36 = (7b -6)(7b +6)
so because there you missed some signs in these wrote choices
hope helped
Step-by-step explanation:
Answer:
6y² - 20y + 6
Step-by-step explanation:
Use FOIL method
(3y - 1)(y-3) = 3y*y + 3y*(-3) + (-1)*y + (-1)*(-3)
= 3y²- 9y - y + 3 {add the like terms}
= 3y² - 10y + 3
2(3y - 1)(y - 3) = 2 ( 3y² - 10y + 3)
= 2*3y² - 2*10y + 2*3
= 6y² - 20y + 6